脳血管障害の治療の進歩 - 平野, 照之 (神経治療学, 2022)
「I. 脳梗塞の急性再開通療法」「1. 機械的血栓回収療法前の血栓溶解薬前投与の意義」2020年のDIRECT-MT(Direct Intraarterial thrombectomy in order to Revascularize acute ischemic stroke patients with large vessel occlusion Efficiently in Chinese Tertiary hospitals : a Multicenter randomized clinical Trial)に引き続き, DEVT(Direct endovascular thrombectomy vs combined IVT and endovascular thrombectomy for patients with acute Large Vessel Occlusion in the anterior circulation), SKIP(Randomized study of endovascular therapy with versus without intravenous tissue plasminogen activator in acute stroke with ICA and M1 occlusion), MR CLEAN-NOIV (Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands - NOIV)の最終結果が論文発表され, SWIFT-DIRECT, DIRECT-SAFEも主要国際学会で結果が開示(論文発表は2022年)された.